2023
DOI: 10.1021/acs.jpcc.2c07467
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Surface Intrinsic Resilience against Bubble Coverage Using Localized Electrochemical Impedance Spectroscopy Time Domain Information

Abstract: Bubble coverage on electrode surfaces presents challenges for the wide application of water electrolysis technology. Earlier experimental studies on superaerophobic electrode surfaces indicated that surface roughness of microscale morphologies can greatly increase the surface’s resilience against bubble coverage at high current densities. Localized electrochemical impedance spectroscopy (LEIS) is used in this paper to assess this surface conductance under bubbles. The local impedance of the bubble-shielded are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Therefore, it is necessary to use various methods to avoid the prolonged attachment of bubbles and reduce their effect on efficiency. Wang et al 14 found that bubbles mainly caused the increase in impedance of the bilayer by using localized electrochemical impedance spectroscopy. Moreover, the use of electrodes with a large porosity and a uniform distribution of voids can effectively reduce the impedance of bubbles.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to use various methods to avoid the prolonged attachment of bubbles and reduce their effect on efficiency. Wang et al 14 found that bubbles mainly caused the increase in impedance of the bilayer by using localized electrochemical impedance spectroscopy. Moreover, the use of electrodes with a large porosity and a uniform distribution of voids can effectively reduce the impedance of bubbles.…”
Section: Introductionmentioning
confidence: 99%
“…At 2.5 V, the Ionomer-Ir electrode shows a current density (2278 mA cm –2 ) 23.2% lower than that of the pristine Ir electrode (2966 mA cm –2 ). Through measurement of the EIS at 1.7 and 2.0 V, the difference in the fitted first semicircles indicated that the ionomer coverage does not decrease but rather significantly enhances the charge transfer on the Ir surface (Figure b,c) . This indicates the substantial performance loss derived from the increased transport resistance due to the barrier effect of the ionomer.…”
mentioning
confidence: 99%
“…In general, a larger bubble on the catalyst surface brings higher charge transfer resistance, 29,30 and in this kind of microelectrode system, it is embodied as a larger first semicircle. 25 However, although the ionomer significantly increases the size of the bubbles on the Ionomer-Ir surface, as the voltage increases, the existence of an ionomer significantly reduces the charge transfer resistance (Figure 2b,c). This suggests that the ionomer film may decouple the bubble evolution sites from the OER reaction sites and provides additional proton transport paths to the catalyst surface rather than limited transfer through the EDL on the bubble contour and the substrate surface (Figure 4a,b).…”
mentioning
confidence: 99%
See 2 more Smart Citations